2006
DOI: 10.1093/alcalc/agl050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Combined Marker Ggt–cdt and the Conventional Laboratory Markers of Alcohol Abuse in Heavy Drinkers, Moderate Drinkers and Abstainers

Abstract: GGT-CDT improves the sensitivity of detecting excessive ethanol consumption as compared with the traditional markers of ethanol consumption. These findings should be considered in the assessment of patients with alcohol use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 30 publications
3
74
0
3
Order By: Relevance
“…Also, EtG has recently been suggested as a marker of chronic high alcohol intake, measured in hair (64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76). According to the research so far, the sensitivity and specificity exceeds that of the traditional markers for chronic high alcohol intake, like the liver enzymes aspartate aminotranserase (AST), alanine aminotransferase (ALT) and gamma-glutamyl transferase (GGT) as well as carbohydratedeficient transferrin (CDT) (34,35,(77)(78)(79)(80).…”
Section: Non-oxidative Metabolism Of Ethanol; Ethyl Glucuronide and Ementioning
confidence: 99%
“…Also, EtG has recently been suggested as a marker of chronic high alcohol intake, measured in hair (64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76). According to the research so far, the sensitivity and specificity exceeds that of the traditional markers for chronic high alcohol intake, like the liver enzymes aspartate aminotranserase (AST), alanine aminotransferase (ALT) and gamma-glutamyl transferase (GGT) as well as carbohydratedeficient transferrin (CDT) (34,35,(77)(78)(79)(80).…”
Section: Non-oxidative Metabolism Of Ethanol; Ethyl Glucuronide and Ementioning
confidence: 99%
“…Such circumstances led us to not use a quantity-frequency survey for detecting hazardous drinking but instead to use the total AUDIT (Alcohol Use Disorders Identification Test) score and/or %CDT. The main reasons for choosing these tools were as follows: a) several research papers have shown that the AUDIT is the most effective tool for identifying subjects with hazardous levels of drinking 23) , and b) although alcohol consumption continues to rise in most developed countries, those subject to hazardous drinking escape clinical diagnosis, so it is widely accepted that biochemical markers are useful for sensitive and effective detection of real alcohol consumption 24) , with %CDT being the only marker test approved by the FDA for the identification of hazardous drinking 25) . In our study, the proportion of workers that were screened as positive for one or both of the AUDIT and CDT tests was 13.8%.…”
Section: Discussionmentioning
confidence: 99%
“…New biomarkers that have high specificity and sensitivity are increasingly being used today. One of them is CDT, the first test to be approved in the USA by the FDA (Food and Drug Administration) as the biomarker for alcoholism (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%